Spectrum of preventive antibacterial therapy of Lyme disease - Bilokobyla, S. O.; Білокобила, Світлана Олександрівна (My University, 2024)
The aim of the research is to analyze the range of antibacterial drugs used for the prevention of Lyme disease in persons affected by tick bites.